Etnofisika Permainan Tradisional Dodorobe Sebagai Pengembangan Bahan Ajar Fisika - Haryati Mahyudin; Siti Nahria Hasan (JIPFRI (Jurnal Inovasi Pendidikan Fisika dan Riset Ilmiah), 2024)
The purpose of this study is to produce physics teaching materials related to the Dorobe game that are suitable for use by high school students and to find out the students' response to the teaching materials developed. The research was conducted in a small group of 15 students from SMA Negeri 6 Ternate. The method used in this study is a 4D development study which includes four stages, namely definition, design, development, and dissemination through an ethnographic approach to examine the physical concepts contained in the dodorobe game. The data analysis technique in this study is the Likert scale. As a result of this study, the average percentage of physics teaching materials based on evaluation by material expert validators was 72.5%, the average percentage of assessment by media validators was 87.5%, and the students' response to the teaching materials developed based on linguistic, material and appearance aspects was very good with a score of 80.9%. For this reason, physics teaching materials in the traditional game of dodorobe are feasible in the process of learning physics on impulse and momentum materials.